Phenomenology, humanization and health promotion: an articulation proposal - Gomes, Annatália Meneses de Amorim; Paiva, Eliana Sales; Valdés, Maria Teresa Moreno; Frota, Mirna Albuquerque; Albuquerque, Conceição de Maria de (Saúde e Sociedade, 2008)
This is an essay about possible articulations between phenomenology, humanization and health promotion. Phenomenology is the study of the description of human phenomena and their meanings. Phenomenological research in the healthcare field has been strengthened during the last years, motivated by the need to apprehend the meanings of each subject inserted in the context of his/her cultural and historical wholeness. As a criticism to the biomedical model, it has encouraged the emergence of Health Phenomenology and the new production in health care. Phenomenology is proposed here as an important methodological resource for the understanding of the humanization process in the healthcare and health management areas, due to the consonance with the perspective of integrality, autonomy and enlarged view of the health/illness process, by means of its presuppositions of phenomenon totality, intentional conscience and ethics.